Childhood Context Explains Cultural Variance in Implicit Parenting Motivation: Results from Two Studies with Six Samples from Cameroon, Costa Rica, Germany, and PR China. (1st April 2014) - Chasiotis, Athanasios; Bender, Michael; Hofer, Jan
We investigated the effect of the childhood context variables number of siblings (study 1 and 2) and parental SES (study 2) on implicit parenting motivation across six cultural samples, including Africa (2xCameroon), Asia (PR China), Europe (2xGermany), and Latin America (Costa Rica). Implicit parenting motivation was assessed using an instrument measuring implicit motives (OMT, Operant Multimotive Test;Kuhl and Scheffer, 2001 ). Replicating and extending results from previous studies, regression analyses and structural equation models show that the number of siblings and parental SES explain a large amount of cultural variance, ranging from 64% to 82% of the cultural variance observed in implicit parenting motivation. Results are discussed within the framework of evolutionary developmental psychology.